ChemInform Abstract: Paramagnetic Ionic Liquids for Advanced Applications: A Review. Issue 37 (August 2016) - Joseph, Aswathy; Zyla, Gawel; Thomas, Vibin Ipe; Nair, P. Radhakrishnan; Padmanabhan, A. S.; Mathew, Suresh
Abstract: Review: 98 refs.